Technological Innovation and Environment Degradation in South Asian Countries - Ayesha Naz; Muhammad Ejaz (Sir Syed University Research Journal of Engineering and Technology, 2022)
This study is an attempt to analyze the impact of technological innovations on Environmental Degradation (ED) in selected South Asian countries over the period 1996 to 2019. The limited and inconclusive result on the association between technological innovation and the environment particularly in South Asia provides an impetus to explicitly reexamine this relationship. The current study is unique in using various greenhouse gases to measure environmental degradation. Moreover, technology is also bifurcated into all other technological innovations and environment-related technology (eco-innovation). Panel robust least square is used to obtain the results. The outcome shows that technological innovations and GDP is contributing to CO2 emissions. It means that these two variables have an unfavorable influence on the environment. However, eco-innovations appeared to be significant in reducing CO2 emissions and other greenhouse gases. Hence, eco-innovations are desirable to lessen the negative consequences on the environment. Low carbon technologies redefine the production and consumption pattern to offset the environmental damaging trend. Carbon emission rates critically depend on the future direction of technological innovations, hence, this study suggests increasing the degree of eco-innovations to protect the environment.